ANALISIS SENTIMEN PENGGUNA APLIKASI DANABERDASARKAN ULASAN PADA GOOGLE PLAY STOREMENGGUNAKAN METODE SUPPORT VECTOR MACHINE - Abitdavy Athallah Muhammad, (2022)
The development of technology in this era is very rapid, one of the fields that is very developed are finance. One of the digital financial products are electronic money. Several companies from fintech applications are starting to emerge, and one of them is DANA. From the convenience offered, many oepople have started using apllication DANA. And because there are more users, more and more users provide the experience of using it in the form of satisfaction and complaints in reviews on the Google Play Stores. Reviews from users can be used as material for analysis so that they can be input or feedback to interested companies so that they can be improved in the future. In this study the data obtained from user reviews of the DANA digital wallet application on the Google Play Store. The data review is divied into 2 categories, namely positive and negative data based on manual labeling by 3 anatators. Support Vector Machine method and chi square feature selection are used in model making. The evaluation results are 87,58%, precision is 91,20%, and recall is 90,21% for the SVM model, while for the SVM - chi square model, the accuracy is 89,41%, precision is 93,29% and recall by 90,76%.